Importance Of Culture In managing Employee Expectation during An Acquistion: A Case Study Approach - Avinash, V. Kothari (2010)
The role of culture in Mergers and Acquisitions (M&A) is often overlooked. Research has suggested that many failures in M&A have been attributed to the incompatibility in culture of the merging organizations. This Individual Management report provides an in-depth analysis on the culture there which was one of the four key outcomes of Group Management report titled: “Managing Employee Expectations during an Acquisition: A Case Study Approach.”.Based on the analysis performed, it can be concluded that the cultural aspect in the case of ACons has been overlooked. The primary failure with regards to the cultural integration within ACons can be attributed to the lack of detailed planning and adequate assessment of cultural related issues. The findings also revealed that inadequate planning to the type of organizational culture to adopt after the acquisition was not established and hence could have been a contributing factor in the acquisition process not proceeding the way it was intended to. If an adequate plan had been in place, it’s likely that the changes within the new combined organization would have been more readily accepted. It is anticipated that if the acquisition had considered the human and cultural aspect, the acquisition could have been a success. However, managing expectations of employees during this trying times does not solely lie in the hands of culture alone. The other key themes identified in the Group Management report such as leadership, Human Resource and Communication need to be considered in parallel to ensure success of the acquisition process. In order to ensure that future cultural clashes between ACons and AComp are identified well ahead of time, it is recommended to perform a cultural audit on a regular basis. This will allow ACons to take stock of the environment within the organization and with that information administer the necessary change ffectively.